Establishment and Characterization of a HER2-Positive Cell Line Derived From the Pleural Effusion of a Drug-Resistant Breast Cancer Patient - Li, Zhaoqing; Zhuo, Wenying; Chen, Lini; Zhang, Xun; Chen, Cong; Hu, Dengdi; Chen, Yongxia; Yang, Jingjing; Zhou, Yulu; Mao, Misha; Xu, Ling; Ju, Siwei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Drug resistance is a daunting challenge in the treatment of breast cancer, making it an urgent problem to solve in studies. Cell lines are important tools in basic and preclinical studies; however, few breast cell lines from drug-resistant patients are available. Herein, we established a novel HER2-positive breast cancer cell line from the pleural effusion of a drug-resistant metastatic breast cancer patient. This cell line has potent proliferative capability and tumorigenicity in nude mice but weak invasive and colony-forming capability. The molecular subtype of the cell line and its sensitivity to chemotherapeutics and HER2-targeting agents are different from those of its origin, suggesting that the phenotype changes between the primary and metastatic forms of breast cancer.